RESPONS BERBAGAI POPULASI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt.) TERHADAP PEMBERIAN PUPUK UREA - Usman Made (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
The research aimed at identifing the respons of various population of sweet corn plant on urea fertilizer application.  The research was carried out in Solowe, Sigi Biromaru sub district, Donggala regency from September to December 2007.  The research used a Randomized Block design in a factorial experiment.  The first factor was urea fertilizer (P) consisted of 200 kg/ha (p1), 300 kg/ha (p2), and 400 kg/ha (p3).  The second factor was plant population (J) included one plant per cluster (j1), two plants per cluster (j2), and three plants per cluster (j3).  There were 9 combinations of treatments with three replicates for each treatment.  Therefore, there were 27 experimental units.  The research results showed that both the urea fertilizer and plant population had significant influence on all parameter observed but tassel flowering.  Whereas the interaction between the two factors was significantly influenced the seed number per cob and cob weight per cluster.  The application of 400 kg/ha urea fertilizer improved the growth quality of sweet corn as shown by larger stem diameter, longer and bigger cob, and kernel number per cluster. Population with one plant per cluster resulted in higher yield.  Increasing plant number per cluster significantly reduced plant yield.  There was interaction effect between plant population and urea fertilizer rate on kernel number per cob and cob weight per cluster.